Natural Science Mini-Project Practicum E-Module to Enhance Higher-Order Thinking, Science Process Skills, and Scientific Attitudes - Bakhtiar Ardiansyah; Agus Ramdani; Aliefman Hakim; Muh. Makhrus; Shafinah Kamarudin; Na Jiang (Online Learning In Educational Research (OLER), 2025)
Science learning in schools still rarely uses natural science mini-project practicums packaged in the form of e-Modules. This study aims to 1) develop a Natural Science Mini-Project Practicum E-Module that is suitable for improving critical thinking skills (HOTS), science process skills (SPS), and scientific attitudes (SA). 2) determine the effect of the E-Module on the dependent variable. This study uses a 4D model with a trial involving 115 students (37 students in a limited trial and 78 students in a large-scale trial) at SMP Negeri 17 Mataram. The instruments consisted of multiple-choice questions, observation sheets, and questionnaires. Data were analyzed using the percentage of validity and practicality, N-Gain, prerequisite tests, and hypothesis testing. The results showed that the E-Module was valid (3.69), practical (3.37), and effective in improving HOTS (70.87), SPS (72.27), and SA (70.54) with high criteria. The results of the HOTS (0.000), SPS (0.001), and SA (0.003) hypothesis tests obtained significance values ​​below 0.05. Thus, this e-module is feasible and effective for science learning.